The Properties of Solvent-Based and Water-Borne Butyl Acrylate/Styrene Copolymer Films - Yi Wang; Zhonghua Chen (Advances in Polymer Technology)
With the increasing demands of environmental protection, the properties of water-borne coatings film must meet or exceed current solvent-based coatings. It is an important part of coating science for characterizing the film properties of polymers which was used in the water-borne and the solvent-based coating. In this study, UV-visible spectroscopy, gravimetric analysis, scanning electron microscopy, and electrochemical impedance spectroscopy were used to characterize the properties of the water-borne and the solvent-based poly(butyl acrylate/styrene) (P(BA/St)) copolymer films. The water-borne and the solvent-based P(BA/St) copolymer was synthesized by two methods. The copolymer had a Tg of approximately 14.4°C, which was close to room temperature. The water-borne copolymers were prepared via a three-step film formation process, while the solvent-based copolymer films were prepared in two steps. Comparing the properties of the water-borne and the solvent-based films, the water absorption capacities decreased with increasing film formation times, and the film barrier properties and electrochemical properties of both films improved as the film formation time increased.